Factors Affecting the Quality of SKPD Financial Reports in Cimahi City Local Government - Indra Firmansyah Bagjana; Andry Arifian Rachman (Jurnal ASET (Akuntansi Riset), 2021)
The objective of this research is to determine the influence of Human Resource Competence and Government Internal Control System on the Quality of SKPD Financial Reports in the Cimahi City Local Government.  The research was conducted on all SKPD, with 83 respondents who are the team of SKPD financial report compilers. To determine the effect of Human Resource Competence and Government Internal Control System on the Quality of SKPD Financial Reports, multiple linear regression models and t-test to examine the hypothetical tests processed with SPSS Statistics 25 were used.  The results showed that the competence of human resources and the government's internal control system had a significant effect on the quality of SKPD's financial reports.